Mexico : Financial Sector Assessment Program Update; Technical Note; Observance of the Core Principles for Systemically Important Payment Systems; An Update. (IMF Staff Country Reports; Country Report, 2007)
This paper presents a technical note on Mexico's Observance of the Core Principles for Systemically Important Payment Systems. The Bank of Mexico has issued regulation to support check truncation, the use of electronic signatures, and regulation that endorses the development and implementation of new payment instruments. In the area of retail payments, progress has been made to improve the fragmented infrastructure and enlarge the connectivity and interoperability of the different networks of commercial banks.